Barriers to adoption of industry 4.0 and sustainability: a case study with SMEs - Kumar, Shashank; Raut, Rakesh D.; Aktas, Emel; Narkhede, Balkrishna E.; Gedam, Vidyadhar V. (Taylor & Francis, 2023)
The concepts of sustainable supply chains and Industry 4.0 are progressively getting attention in different domains. Companies have started developing and implementing these practices in their business models. However, several challenges influence the adoption of sustainability and Industry 4.0 (I4.0) in small and medium-sized enterprises (SMEs). This study aims (i) to identify the adoption barriers of sustainability and I4.0 and (ii) establish the interrelationship among these barriers for SMEs. An extensive literature search supported by interviews with supply chain practitioners from three SMEs identified 12 critical barriers to adoption. The barriers are then ranked using “Interpretive Structural Modeling.” The results suggest that the “lack of resources” and the “lack of employee’s competence/experts” are the most influencing barriers. Changing government regulations on the allocation of capital and financial incentives for SMEs to encourage training and skills development programs could promote sustainable supply chains and practices. The study also reflects short-, medium- and long- term planning strategies for supply chain practitioners for adoption of sustainability and I4.0 in SMEs.
Keywords: Supply chain; Sustainability; Barriers; Sustainable and Industry 4.0; Interpretive Structural Modeling; SMEs